The Mater-Bi® biodegradable film for strawberry (Fragaria x ananassa Duch.) mulching: effects on fruit yield and quality - Morra, Luigi; Bilotto, Maurizio; Cerrato, Domenico; Coppola, Raffaella; Leone, Vincenzo; Mignoli, Emiliana; Pasquariello, Maria Silvia; Petriccione, Milena; Cozzolino, Eugenio (Italian Journal of Agronomy, 2016)
Two trials in different agricultural farms were carried out from October 2014 to June 2015 with the aim to assess the advantages linked to the substitution of the low density polyethylene (LDPE) films for soil mulching with the Mater-Bi® biodegradable films in the strawberry cultivation under tunnel in Campania. Lifetime of biodegradable mulch and influence of type of mulch on the yield and the quality of cvs Sabrina and Fortuna were evaluated. Plants were cultivated on mulched, raised beds, high 40 cm from bottom soil. Mater-Bi® film was 20 µm thick while LDPE film was 50 mm thick. The physical-chemical parameters (firmness, pH, total soluble solid content, titratable acidity and skin colour) and some bioactive compounds (total polyphenols, flavonoids, anthocyanins, antioxidant activity) of fruits were determined by three samplings effected in consecutive months (from March to May 2015) of the harvest cycle. Biodegradable film guaranteed an effective mulch along the whole strawberry cycle (9-10 months including the time of drawing up of film). Yields of cv Sabrina on LDPE was 18% higher than those on Mater-Bi® while the opposite was detected in cv Fortuna (+10%). The physical-chemical parameters of fruits were not modified by the mulches. The content of the bioactive compounds, instead, resulted, in each time of sampling, significantly higher in fruits picked on Mater-Bi® based film.